IDENTIFIKASI POTENSI KEARIFAN LOKAL MASYARAKAT GOLEWA KABUPATEN NGADA SEBAGAI UPAYA PENGEMBANGAN DI BIDANG PENDIDIKAN - Maria Waldetrudis Lidi; Ningsih; Yasinta Yenita Dhiki (Program Studi Pendidikan Fisika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Flores, 2020)
The objective of this research are (1) to find out the potentials of Golewa community local wisdom which related to education , and (2) To describe the meaning of Golewa local wisdom which related to education. The procedures have done in this research, (1) analysing the local wisdom potentials by using Miles and Huberman technique. The potentials of Ngada community local wisdom found such as Paruwitu, Trima, Adho/Wela Koti, and Kosubue. That local wisdom able to use in teaching and learning process based on topic of learning. Keywords : Local Wisdom, Golewa Community, Education